2018
DOI: 10.1101/449199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local vulnerability and global connectivity jointly shape neurodegenerative disease propagation

Abstract: It is becoming increasingly clear that brain network organization shapes the course and expression of neurodegenerative diseases. Parkinson's disease (PD) is marked by progressive spread of atrophy from the midbrain to subcortical structures and eventually, to the cerebral cortex. Recent discoveries suggest that the neurodegenerative process involves the misfolding and prion-like propagation of endogenous α-synuclein via axonal projections. However, the mechanisms that translate local "synucleinopathy" to larg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 72 publications
4
50
0
Order By: Relevance
“…More generally, the present findings are part of a larger trend in the field to understand structure-function relationships by considering molecular [4,28,77,107], cellular [3,70,81,83] and physiological [25,82] attributes of network nodes, thereby conceptually linking local and global brain organization [55,89]. In such "annotated networks", macroscale network architecture is thought to reflect similarity in local properties, and vice versa, such that areas with similar properties are more likely to be anatomically connected and to functionally interact with one another [11,42,46,104].…”
Section: Discussionmentioning
confidence: 61%
“…More generally, the present findings are part of a larger trend in the field to understand structure-function relationships by considering molecular [4,28,77,107], cellular [3,70,81,83] and physiological [25,82] attributes of network nodes, thereby conceptually linking local and global brain organization [55,89]. In such "annotated networks", macroscale network architecture is thought to reflect similarity in local properties, and vice versa, such that areas with similar properties are more likely to be anatomically connected and to functionally interact with one another [11,42,46,104].…”
Section: Discussionmentioning
confidence: 61%
“…In neurodegenerative diseases, transneuronal transport of toxic misfolded proteins is associated with cell death and atrophy (6,63,64). As a result, patterns of atrophy in neurodegenerative diseases often resemble structural and functional network patterns (65), a result that has been reported in Alzheimer's disease (8,66,67), Parkinson's disease (9,10,68), and amyotrophic lateral sclerosis (69).…”
Section: A Spreading Hypothesis Of Schizophrenia?mentioning
confidence: 96%
“…By far, most work in this area has focused on understanding GM volume reductions in clinical disease. Not only have several meta-analyses of different diseases shown that such reductions are common (Fornito et al, 2009;Bora et al, 2010Bora et al, , 2011Bora et al, , 2012aFusar-Poli et al, 2011;Hallahan et al, 2011;Linkersdörfer et al, 2012;Du et al, 2012;Li et al, 2014Li et al, , 2018Stoodley, 2014;Cauda et al, 2014;Foster et al, 2015;Lin et al, 2016;Wise et al, 2017;Wu et al, 2018), and other work suggests that anatomically distributed yet coordinated GM reductions are tied to the underlying connectivity between regions (Seeley et al, 2009;Raj et al, 2012;Zhou et al, 2012;Crossley et al, 2014;Iturria-Medina et al, 2014;Zeighami et al, 2015, Cauda et al, 2018aYau et al, 2018;Zheng et al, 2019). In contrast, GM increases are less commonly considered in clinical neuroimaging studies (Cauda et al, 2011(Cauda et al, , 2017(Cauda et al, , 2018bTatu et al, 2018, Cauda et al, 2019bDing et al, 2019;Lu et al, 2019), potentially because they might be a rarer consequence of disease and because they can be difficult to explain in the context of pathology.…”
Section: Introductionmentioning
confidence: 99%